The Jamaican leviathan : a musical comedy (Kingston : Derrick Harriott, 1989)
"Once upon a time, in a faraway land" that's how the story begins ... "In a town called Tamrin'ville just outside the woods of Cascadia". A bridge links Tamrin'ville and Cascadia, and beneath this bridge lives a man-eating alligator ... a Leviathan. As the plot unfolds, we discover the problems caused by this monster and we meet the inhabitants of Tamrin'ville and Cascadia. The inhabitants of these towns are troubled for years until the visit of a young wanderer, in search of his destiny. He transforms life for the simple folk terrified by the monster alligator. The story of how the villagers are eventually rid of the fearful creature is filled with moments of touching romance, nail-biting excitement and rippling adventure.
Ninety (90) minutes.
Produced by Beverly Ulett ; Executive Produced by Derrick Harriott ; Directed by Cathi Levy.
Keywords: Fairy tales -- Jamaica; Musical -- Jamaica; Fairy tales; Jamaica